IMPLEMENTASI KEBIJAKAN BLT DANA DESA DALAM PENANGGULANGAN KEMISKINAN DI DESA PULAU KECIL KABUPATEN INDRAGIRI HILIR - risma nurhalizah; ahmad hadi (Jurnal Ilmu Administrasi Negara, 2026)
This study aims to analyze the implementation of the Village Fund Direct Cash Assistance (BLT Dana Desa) policy in Pulau Kecil Village, Indragiri Hilir Regency, as a local-level instrument for poverty alleviation. Although this policy is designed to improve community welfare, particularly in the post-pandemic context and amid economic instability, its implementation continues to face various challenges. This study employs a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving village officials and beneficiary communities as key informants. The findings reveal that the implementation of the BLT Dana Desa policy remains suboptimal. Key issues include inaccurate targeting of beneficiaries, low validity and reliability of socio-economic data, and limited community participation in village deliberation processes. Furthermore, the transition to a non-cash distribution system through banking mechanisms has created accessibility barriers for certain groups. These findings indicate a significant gap between policy design and field-level realities. This study concludes that policy effectiveness is strongly influenced by data governance quality, institutional capacity at the village level, and the degree of community participation. Therefore, strengthening transparency, improving data validation, and adopting a more adaptive and context-sensitive implementation approach are essential to ensure that the BLT Dana Desa policy operates effectively, accurately targeted, and sustainably.